DAMPAK PANDEMI COVID-19 TERHADAP AGROINDUSTRI TEMPE: APAKAH MENURUNKAN PENDAPATAN PRODUSEN? - Mega Puspita Sari; Anik Suwandari (University of Jember, 2022)
Covid-19 pandemic on the tempe agroindustry in Ponorogo. The research method uses analytical and comparative methods. Determination of the sample using the purposive sampling method with certain criteria. This research uses paired t-test and income analysis. The results showed that the volume of soybean use in the tempe agroindustries in Ponorogo Regency after the covid-19 pandemic decreased. The paired t-test analysis results showed differences in the volume of soybean use after the covid-19 pandemic. In addition, the average value of income obtained by the tempe agroindustries in the Ponorogo Regency has decreased. There is a significant difference in income before and after the covid-19 pandemic in the tempe agroindustries in Ponorogo Regency.